The effect of differentiation in the initial angle of the hip joint on squat jump performance - Hara, T.; Tachi, M.; Yokozawa, S.; Hirano, Y. (Japanese Journal of Elite Sports Support, 2009)
The purpose of this study was to quantify the effect of the differences in the initial angles of hip joint on squat jump performance, and in order to provide this useful knowledge for athletic training and physical fitness tests. Twenty three subjects performed maximum effort squat jumps from three different initial hip joint angles: the largest hip joint angle (SJL), the voluntary selected hip joint angle which the subjects thinks optimum (SJV) and the smallest hip joint angle (SJS). The subjects jumped on a switch mat (1000Hz) and all of their performances were captured with a video camera (60Hz). Jump height and the initial joint angle of each lower extremity were calculated using kinematic data. Multiple comparison was used to analyze the statistical differences between SJL, SJV and SJS in jump height and each initial joint angle. The values of the initial hip joint angle in SJL, SJV and SJS were 91.6+/-13.3, 70.0+/-19.5 and 49.7+/-11.0 deg, respectively, and significant differences were observed in the following pairs of conditions: SJL>SJS, SJV>SJS and SJL>SJV. The value of the voluntary initial angle of the hip joint (SJV) was about the angle intermediate between SJS and SJL. On the other hand, the values of the jump height in SJL, SJV and SJS were 0.34+/-0.05, 0.37+/-0.04 and 0.40+/-0.06 m, respectively, and significant differences were observed in the following pairs of conditions: SJL<SJS (17.6% increase), SJV<SJS (8.1% increase) and SJL<SJV (8.8% increase). These results suggested that, of the three jumping conditions, the best performance was obtained when the subject jumped from the smallest hip joint angle, and was not from the voluntary selected initial positions which the subjects thought optimum.